Chemokines as the critical factors during bladder cancer progression: an overview. (3rd September 2021) - Zangouei, Amir Sadra; Hamidi, Amir Abbas; Rahimi, Hamid Reza; Saburi, Ehsan; Mojarrad, Majid; Moghbeli, Meysam
Abstract: Bladder cancer (BCa) is one of the most frequent urogenital malignancies which is mainly observed among men. There are various genetic and environmental risk factors associated with BCa progression. Transurethral endoscopic resection and open ablative surgery are the main treatment options for muscle invasive BCa. BCG therapy is also employed following the endoscopic resection to prevent tumor relapse. The tumor microenvironment is the main interaction site of tumor cells and immune system in which the immune cells are recruited via chemokines and chemokine receptors. In present review we summarized the main chemokines and chemokine receptors which have been associated with histopathological features of BCa patients in the world. This review highlights the chemokines and chemokine receptors as critical markers in early detection and therapeutic purposes among BCa patients and clarifies their molecular functions during BCa progression and metastasis.